PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN, DAN LOCUS OF CONTROL TERHADAP PERILAKU KEUANGAN MAHASISWA PRODI MANAJEMEN UNIVERSITAS MUHAMMADIYAH GRESIK - Safira Cahyani Ula Muhidia (Jurnal Manajerial, 2019)
This study aims to test the Influence of Financial Knowledge, Financial Attitudes, and Locus Of Control Against Student Financial Behavior Management Study University of Muhammadiyah Gresik. The object of this research is the students of S1 Study Program of Muhammadiyah University Gresik. A total of 191 respondents were selected based on the proportionate stratified random sampling method. Hypothesis testing is done by using multiple linear regression analysis with SPSS program 19. The results showed that the financial knowledge variable has no effect on financial behavior. While the financial attitude and locus of control have a significant positive effect on financial behavior.